2009
DOI: 10.1002/dev.20388
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory learning in the rat immediately after birth: Unique salience of first odors

Abstract: An infant rat’s chance of survival is increased when it remains close to the nest. Early olfactory learning supports such adaptive behavior. Previous experiments indicated that non-associative odor exposure immediately after birth promoted later attachment to a similarly scented artificial nipple. The goal of the current experiments was to extend these findings on olfactory learning in the hours after birth by: exposing pups to more than one odor exposure (Exp. 1), dissecting the role of timing versus order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…For example, the primary olfactory system (including the olfactory bulb and piriform cortex) is functional at birth in rodents (Brunjes, 1994, Miller and Spear, 2009, Sarma et al, 2011), and in fact is necessary for infant survival (Moriceau and Sullivan, 2004). In contrast, the hippocampal formation which receives robust olfactory input via the entorhinal cortex, is a relatively late developing system with hippocampal-dependent behaviors not emerging until near weaning in rodents (Freeman et al, 1994, Rudy, 1994, Raineki et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the primary olfactory system (including the olfactory bulb and piriform cortex) is functional at birth in rodents (Brunjes, 1994, Miller and Spear, 2009, Sarma et al, 2011), and in fact is necessary for infant survival (Moriceau and Sullivan, 2004). In contrast, the hippocampal formation which receives robust olfactory input via the entorhinal cortex, is a relatively late developing system with hippocampal-dependent behaviors not emerging until near weaning in rodents (Freeman et al, 1994, Rudy, 1994, Raineki et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments did not find consistent sex effects in olfactory learning immediately after birth (Miller & Spear, 2008, 2009). Therefore, although sex was evenly distributed across groups, this was not a factor in the present design.…”
Section: Methodsmentioning
confidence: 57%
“…Sensitization, or increased responsiveness after successive exposures, is unlikely however since previous experiments have found that animals given two odor exposures prior to activity testing did not exhibit levels of activity higher than pups with only one odor exposure (Miller & Spear, 2009). Given the apparent lack of odor specificity in the effect of such neonatal odor exposure (Miller & Spear, 2009), it is also possible that such responding could indicate odor-induced neurophysiological changes in the olfactory bulb. Yet, odor recognition and neural changes in the olfactory bulb are not mutually exclusive explanations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations